The politics of English : a Marxist view of language - Holborow, Marnie (London ; Thousand Oaks, Calif. : Sage, 1999)
The Politics of English offers a major reappraisal of the way in which language is both shaped by, and contributes to, social life. Taking a classical Marxist approach, the author provides a view of the ideological aspects of language.
Cover; Contents; Acknowledgements; Chapter 1 -- Introduction; Chapter 2 -- In the Beginning was Society: Marx, Volosinov and Vygotsky on Language; Chapter 3 -- Money Talks: The Politics of World English; Chapter 4 -- Women, Language and the Limits of Feminism; Chapter 5 -- The Politics of Standard English; Chapter 6 -- Conclusion; Bibliography; Index
Includes bibliographical references (pages 197-211) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Language and languages -- Political aspects; English language -- Political aspects; Language and languages -- Philosophy; Women -- Language; Philosophy, Marxist; Langage et langues -- Aspect politique; Langage et langues -- Philosophie; Femmes -- Langage; Philosophie marxiste; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General; English language -- Political aspects; Language and languages -- Philosophy; Language and languages -- Political aspects; Philosophy, Marxist; Women -- Language; Taalpolitiek; Engels; Politieke aspecten; Englische Sprache -- Politik; Politik -- Englische Sprache